A Mixed-Methods Exploration of Mastery Goal Support in 7th-Grade Science Classrooms. Issue 2 (3rd April 2023) - Liu, Pei Pei; McKinney, David; Lee, Alexandra A.; Schmidt, Jennifer A.; Marchand, Gwen C.; Linnenbrink-Garcia, Lisa
Abstract: Mastery goal structures, which communicate value for developing deeper understanding, are an important classroom support for student motivation and engagement, especially in the context of science learning aligned with the Next Generation Science Standards. Prior research has identified key dimensions of goal structures, but a more nuanced examination of the variability of teacher-enacted and student-perceived goal structures within and across classrooms is needed. Using a concurrent mixed-methods approach, we developed case studies of how three 7th-grade science teachers enacted different goal structures while teaching the same chemistry unit and how their students perceived these goal structures. Student perceptions were largely consistent with our observational analysis and suggested that a positive social climate and autonomy support are important elements of mastery goal structure. However, balancing socio-emotional support with sufficient academic rigor may be especially important for students with high levels of mastery goal orientation and self-efficacy in science. Implications for research include the need for further research linking classroom stimuli to variability in perceived goal structure, especially across students with different motivational characteristics. Implications for practice include strategies for science teachers to promote perceptions of a mastery goal focus in students, particularly through feedback and recognition practices.